Financing of energy efficiency in public goods: The case of street lighting systems in Indonesia - Muhammad Indra Al Irsyad; Tri Anggono; Rabindra Nepal; Yang Liu; Farhad Taghizadeh-Hesary (Asian Development Bank Institute (ADBI), 2020)
Energy demand growth in Southeast Asian countries is predicted to be the highest in the world, with Indonesia having the highest urbanization rate. Along with growing urban areas, public infrastructures, such as streetlights, are also expanding. Unfortunately, energy conservation measures in public facilities are commonly constrained by the budget limitations of local governments, while the potential participation of an ESCO requires regulation reformation to settle the contradicting regulations. This study proposes several policy recommendations to modify existing guidelines for selecting ESCOs to manage energy efficiency of streetlights in Indonesia. A regulation review and several suggestions for potential improvements for selecting ESCOs are provided. In 2017, the Ministry of Domestic Affairs released a circular letter with a view to solving barriers to ESCO businesses in public sectors; however, the circular letter could be improved in several ways by eliminating the clauses on holders of intellectual property rights, revising the valuation of economic benefit bidding, and increasing the maximum contract period. Moreover, we propose the use of smart streetlighting technologies to improve the value-added services of streetlights and the establishment of a Super ESCO to accelerate ESCO business activity in all economic sectors.
Keywords: G18; H54; H57; H70; L94; Q48; 330; energy conservation; public-private partnership; energy service company; Super ESCO